Male commuters in north and south England: risk factors for the presence of faecal bacteria on hands - Donachie Peter; Cobb Emma; Schmidt Wolf-Peter; Dodrill Laura; Curtis Valerie; de Barra Mícheál (BMC, 2011)
Abstract Background A previous study found that the prevalence of contamination with bacteria of faecal-origin on the hands of men differed across UK cities, with a general trend of increased contamination in northern cities. The aim of this study was to (1) confirm the north-south trend (2) identify causes for the trend. Methods Hand swabs from commuters (n = 308) at train stations in 4 cities were tested for the presence of faecal bacteria. Results The prevalence of hand contamination with faecal bacteria was again higher in cities in the north compared to the south (5% in London, 4% in Birmingham, 10% in Liverpool and 19% in Newcastle). Contamination risk decreased with age and better personal hygiene (self-reported). Soil contact and shaking hands increased contamination with faecal bacteria. However, in multivariable analysis, none of these factors fully explained the variation in contamination across cities. Conclusion The study confirmed the north-south differences in faecal contamination of hands without finding a clear cause for the trend. Faecal contamination of hands was associated with personal hygiene indicators suggesting that microbiological testing may contribute to evaluating hygiene promotion campaigns.